POTENSI PLTMH (PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO) DI KECAMATAN NGANTANG KABUPATEN MALANG JAWA TIMUR - Ikrar Hanggara; Harvi Irvani (Universitas Tribhuwana Tunggadewi Malang, 2017)
Ngantang part of Malang Regency, located at an altitude between 500-700m above sea level. Judging from the topographical conditions, the potential energy of the water used as a source of energy for the MHP in this area is very high. To be able to calculate the potential energy of MHP good electricity necessary to analyze the reliability of river discharge (m3/s), high water fall (meters) and the time of engine operation plan generation (hours). Reliability discharge is obtained by calculating the flow data with FJ.Mock method. Evapotranspiration value in this study using Penman Method. Meanwhile, the data discharge measurements conducted field observations as a discharge control method of calculation results FJ.Mock. Based on the research results obtained in four locations debit mainstay at 0:39 Q60 m3 / sec (Jombok), 1:02 m3 / sec (Waturejo), 0:48 m3 / sec (Ngantru I), 3:14 m3 / sec (Ngantru II). Average large power awakened by calculation is 47.75 K. This amount is equivalent to the fulfillment of the electricity needs of as many as 47 home residences.